Coordinative helix–helix association of heteroleptic metallosupramolecular helicates. Issue 4 (3rd January 2020) - Kang, Philjae; Yoo, Hyojong
Abstract : Coordinative helix–helix association of racemic metallosupramolecular helicates is controllably synthesized and fully characterized. Abstract : The effective incorporation of well-defined coordination spheres, multiple types of ligands (heteroleptic), and specific assembly modes in a given structure enables the fabrication of simplified coordinative supramolecular bio-mimics. Herein, we report the fabrication of a unique racemic macrocycle via association of metallosupramolecular helicates. A nickel (Ni4 ) cluster-based supramolecular helicate, [Ni8 (PDA)6 (CDBA)3 (DMF)2 (H2 O)4 ] (1 ) (PDA = 2, 6-pyridinedicarboxylate, CDBA = 4, 4′-carbonyldibenzoate, DMF = dimethylformamide), is successfully synthesized and fully characterized. Dimerization of right ( P -) and left ( M -) handed helicates of 1 via the coordination of metalloligands, [Ni(PDA2 )] 2− affords {[Ni8 (PDA)6 (CDBA)3 (DMF)4 –Ni(PDA)2 ]2 } (2 ), which can be a representative model of the coordinative helix–helix association of heteroleptic helicates. The solid-state structures of 1 and 2 show high and selective CO2 uptake properties.